An Outcome Evaluation of the Success for Kids Program - Maestas, Nicole (RAND Corporation, 2010)
This report presents results from a multisite, quantitative evaluation of the international Success for Kids (SFK) after-school program. A nonreligious program, SFK seeks to build resilience in children. Interestingly, the authors found that the program positively affected not just social and internal outcomes but also school-related outcomes, even though SFK is not an academic intervention.